2011
DOI: 10.1016/j.snb.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and capturing of antibody affinity ligands: Applications to surface plasmon resonance biochips

Abstract: A surface plasmon resonance (SPR) sensor chip with immobilized protein G was used for simultaneously capturing, purifying and orienting antibody ligands. The ligands were further stabilized by chemical cross-linking. This procedure of designing the sensor chip improved efficient use of the ligands and could prolong the analytical use.The procedure was evaluated on standard dextran-coated sensor chips onto which commercial semi-purified antibodies toward human serum albumin and human troponin where captured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 41 publications
(57 reference statements)
1
37
0
Order By: Relevance
“…The main challenge posed in the successful application of this immobilization technique is surface instability due to affinity interactions, as antibodies coupled to the surface might get displaced by naturally occurring plasma or serum proteins [43]. One way to address this is the use of various bifunctional crosslinking reagents, most commonly dimethyl pimelimidate (DMP) [43,44]. Despite the fact that DMP has been recently replaced by BS3 (bis(sulfosuccinimidyl)suberate) in the majority of protocols for antibody crosslinking to Fc-binding ligands, we opted for DMP to crosslink the secondary antibodies to the immobilized protein A/G since it has been shown that it disrupts less the antigen-binding sites of the Fab region of the antibodies [45].…”
Section: Optimization Of Gopts-protein A/g-modified Surfacesmentioning
confidence: 99%
“…The main challenge posed in the successful application of this immobilization technique is surface instability due to affinity interactions, as antibodies coupled to the surface might get displaced by naturally occurring plasma or serum proteins [43]. One way to address this is the use of various bifunctional crosslinking reagents, most commonly dimethyl pimelimidate (DMP) [43,44]. Despite the fact that DMP has been recently replaced by BS3 (bis(sulfosuccinimidyl)suberate) in the majority of protocols for antibody crosslinking to Fc-binding ligands, we opted for DMP to crosslink the secondary antibodies to the immobilized protein A/G since it has been shown that it disrupts less the antigen-binding sites of the Fab region of the antibodies [45].…”
Section: Optimization Of Gopts-protein A/g-modified Surfacesmentioning
confidence: 99%
“…[162165] However, crosslinkers like DMP may also modify the amine groups on the antigen biding sites, leading to a decrease in antigen binding efficiency. [166] Konrad et. al.…”
Section: Antibody Immobilization Chemistriesmentioning
confidence: 99%
“…These proteins specifically bind to the Fc region of immunoglobulin G (IgG) 1 of many mammalian species, leaving antigen-binding sites of IgG fully available to antigens. For instance, Protein A or Protein G was immobilized on the surface of sensor chips, and antibodies were site-specifically immobilized on the layers of those Fc-binding proteins [6][7][8]. It is also known that the oriented immobilization of Fc-binding proteins on planar surfaces enhances the antigen-binding efficiency of antibodies in comparison to immobilization in a random manner [9,10].…”
Section: Introductionmentioning
confidence: 99%